Modelling and Deliberation of Multireinforcement Surface on Tribothermal Adsorption Performance of Nickel Alloy Matrix Hybrid Nanocomposite. (26th November 2022) - Devi, G. Ramya; Priya, C. B.; Dineshbabu, C.; Karthick, R.; Thanigavelmurugan, K.; Paramasivam, Prabhu
Abstract : The present research work is aimed at developing a nickel alloy (Ni-Cr) matrix hybrid nanocomposite comprising 5 wt%, 10 wt%, and 15 wt% of alumina nanoparticles (Al2 O3 ) size of 50 nm with stable weight percentage (5 wt%) of titanium dioxide (TiO2 ) nanoparticle via vacuum die casting process for an automobile brake pad application. The deliberation of multireinforcement surface on nickel alloy matrix tribological performance was evaluated by constant sliding distance (200 m) on dry sliding condition via rotating pin on disc apparatus with different loading conditions of 10 N, 30 N, 50 N, and 70 N under the sliding velocity of 0.25 m/sec, 0.5 m/sec, and 0.75 m/sec, respectively. The influences of alumina and titanium dioxide nanoparticles in the nickel alloy matrix resulted in the thermal conductivity increasing by 18% compared to unreinforced nickel alloy. After temperature drop, the coefficient of thermal expansion for nickel alloy hybrid composite decreases progressively with increased reinforcement content as 10 wt% Al2 O3 /5 wt% TiO2 . Further inclusion of both Al2 O3 and TiO2 in nickel alloy was increased nominally. The thermal adsorption characteristic on composites mass loss was decreased while temperature increased from 28°C to 1000°C.